Inflation of objectives instead of focus on inflation?: evidence on the ECB objective function from a textual analysis : study supported by the Brigitte Strube Foundation - Heinemann, Friedrich; Kemper, Jan (ZEW-Kurzexpertise, 2022)
In this analysis, we investigate ECB communication by analyzing more than 3,800 speeches from 1999 until 2022. The study measures the attention which ECB Council members pay to various implicit and explicit monetary policy objectives. While price stability, according to the Maastricht Treaty, is the primary objective, other societal objectives can play a role for monetary policy reflections and decisions as well. A changing emphasis on alternative objectives over time but also cross-sectional differences between ECB Council members are an insightful source for current monetary policy debates. In these debates it is discussed to which extent central bank decisions may increasingly be constrained by objectives other than price stability. In addition to price stability, our analysis considers the following dimensions of a possible central bank objective function: financial stability, sovereign bond market stability, public debt, climate protection, and distribution.